2003
DOI: 10.1038/sj.ijo.0802381
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Syndrome: epidemiology and more extensive phenotypic description. Cross-sectional data from the Bruneck Study

Abstract: OBJECTIVES:The present study aimed at evaluating the prevalence of the Metabolic Syndrome and at identifying its additional clinical features. RESEARCH DESIGN AND METHODS: Within a prospective population-based survey examining 888 subjects aged 40-79 y, subjects were identified fulfilling the WHO and the National Cholesterol Education Program-Adult Treatment Panel III (NCEP-ATPIII) criteria for diagnosing the Metabolic Syndrome. In these subjects and in the rest of the sample (controls), several metabolic and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

16
119
7
7

Year Published

2005
2005
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 167 publications
(149 citation statements)
references
References 49 publications
16
119
7
7
Order By: Relevance
“…The prevalence of MetS exceeds 20% in individuals aged 20 or older and 40% in older age groups. 4,[12][13][14][15][16] In the present study, the prevalence was 24.4% in women and 28.7% in men, very similar to that reported in other countries.…”
Section: Discussionsupporting
confidence: 74%
“…The prevalence of MetS exceeds 20% in individuals aged 20 or older and 40% in older age groups. 4,[12][13][14][15][16] In the present study, the prevalence was 24.4% in women and 28.7% in men, very similar to that reported in other countries.…”
Section: Discussionsupporting
confidence: 74%
“…Our finding that metabolic syndrome predicted CVD death is in agreement with results from previous studies in non-diabetic [27][28][29] and type 2 diabetic subjects [30,31]. In the study of Bonora et al [30], no sex-related differences were found in the prediction of CVD among type 2 diabetic patients.…”
Section: Discussionsupporting
confidence: 92%
“…This is because visceral obesity is associated with multiple interrelated disorders, including insulin resistance/diabetes, dyslipidemia, hypertension, and cardiovascular diseases, all of which are subsumed in the term metabolic syndrome (MetS) (Bonora et al, 2003;Nordestgaard et al, 2012). More recently, an association of reduced male fertility and MetS has been proposed (Michalakis et al, 2013).…”
Section: Introductionmentioning
confidence: 99%